1992
DOI: 10.3109/08830189209061788
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Autoreactivity Against Thyroid Stimulating Hormone Receptor

Abstract: The present report identifies an important immunogenic region of the TSH receptor and determinants on the TSH receptor for the two types of autoantibodies seen in hyperthyroid Graves' disease and hypothyroid idiopathic myxedema, TSAbs and TSBAbs, respectively. The immunogenic domain with no important functional determinants, is contained within residues 303-382 and involves residues 352-366 in particular. There are determinants flanking the immunogenic domain on the C-terminal portion of the receptor which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 102 publications
0
27
0
Order By: Relevance
“…15,21,24,25,26 The mechanisms by which viruses in general, and HCV in particular, trigger or enhance autoimmunity can be explained in various ways. 27,28,29,30 According to one theory, viruses may non-specifically trigger immune regulatory cells, such as lymphocytes or macrophages, inducing them to react with self-antigens in multiple organs, and therefore cause tissue injury as well as extrahepatic diseases. Another theory suggests that viruses alter the antigenic profile of infected cells (such as hepatocytes) by changing, releasing or exposing selfantigens that are usually "hidden" and for which the immune system usually has no tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…15,21,24,25,26 The mechanisms by which viruses in general, and HCV in particular, trigger or enhance autoimmunity can be explained in various ways. 27,28,29,30 According to one theory, viruses may non-specifically trigger immune regulatory cells, such as lymphocytes or macrophages, inducing them to react with self-antigens in multiple organs, and therefore cause tissue injury as well as extrahepatic diseases. Another theory suggests that viruses alter the antigenic profile of infected cells (such as hepatocytes) by changing, releasing or exposing selfantigens that are usually "hidden" and for which the immune system usually has no tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Sopedra et al (33), which showed the hyperinducibility of HLA class II expression in thyroid follicular cells from patients with GD, supports a possible role for class II molecules in the development of GD; our present data directly implicate aberrant class II expression as a potential causal factor in the development of stimulating TSHRAbs. Nevertheless, studies of 5'-flanking region cis regulatory elements of the class I and TSHR genes, together with their respective trans factors, suggest the importance of abnormal class I molecules in the expression of GD or other forms of autoimmunity (15)(16)(17)(18) and additionally indicate there are common elements in the class I and class II molecules (18). These findings (15)(16)(17)(18) indicate that both class I and class II molecules are important in the development of GD.…”
Section: Discussionmentioning
confidence: 99%
“…with overexpressed class I or aberrant II, alone or both together, may clarify their respective roles. Thus, greater levels of class II expression in the fibroblasts may increase the frequency of stimulating TSHRAbpositive mice, or increased MHC class I expression, by transfection or a-interferon treatment of the fibroblasts, might enhance the frequency of stimulating TSHRAb-positive mice, since the class I molecule has been shown to be involved in the development of autoimmune diseases (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been extensively and intensively studied for several decades. Abundant clinical and basic studies about TSHR-Ab have been done and have clarified its characteristics, heterogeneity, and clinical significance, and several excellent reviews have been published (1)(2)(3)(4)(5)(6)(7). However, many problems and questions about TSHR-Ab remain unsolved and many new findings have been recently reported.…”
Section: Introductionmentioning
confidence: 99%